Strategi Penerjemahan dan Pergeseran Makna Onomatope pada Lirik Lagu JKT48 - Arisuta, P Citra; Luhur Wedayanti, Ni Putu (Humanis; Vol 22 No 2 (2018)DO - 10.24843/JH.2018.v22.i02.p09, 2018)
Onomatopoeia is a characteristic of Japanese language that is very interesting to learn. However, due to the large number of Japanese onomatopoeias while their counterparts in Indonesian are very limited, sometimes these onomatopoeia become a constraint when the Japanese learner wants to understand more deeply about the meaning of the onomatopoeias. The cultural differences and background of the usages of onomatopoeia in Japan as well as in Indonesia cause problems in the translation process. This research title is “Translation Strategies and Shift of Meaning of Onomatopoeia in JKT48’s Song Lyrics”. The data analysed using descriptive method. This research used the theory of translation strategies by Baker (1992) and componential analysis by Bell (1993). There are seven strategies of translation that used to translate the onomatopoeia . Translation strategy by paraphrase using unrelated words caused the shift of meaning of onomatopoeias . There are five onomatopoeia in four song lyrics that causing the shift of meaning.